2019
DOI: 10.36348/sijap.2019.v02i10.002
|View full text |Cite
|
Sign up to set email alerts
|

A Coorelation Study between ABO blood Group and Type 2 Diabetes Mellitus

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is inherited genetically. There may be an association with blood group as blood group is predetermined genetically. Methods: Two hundred and thirty one (231) diabetic patients are included in the study which conducted by department of physiology. Diabetic patients were taken from medicine department, and the distribution of blood group among apparently healthy blood donors at Department of Immunohematology and Blood Transfusion (IHBT) was taken as control populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Blood group antigens are considered among hereditary indicators, playing a vital role in understanding genetics and disease susceptibility. 25 In recent years, the relationship between blood types and T2DM has been investigated to identify susceptible groups. Although some studies have reported conflicting results, B and O blood types have been associated with increased and decreased risk of developing T2DM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Blood group antigens are considered among hereditary indicators, playing a vital role in understanding genetics and disease susceptibility. 25 In recent years, the relationship between blood types and T2DM has been investigated to identify susceptible groups. Although some studies have reported conflicting results, B and O blood types have been associated with increased and decreased risk of developing T2DM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These studies included a total of 6870 patients with T2DM and 11,890 controls. Eight of the studies were conducted in India, 7,12,13,[22][23][24][25][26] three in Pakistan, [27][28][29] three in Iraq, 8,30,31 two in Ethiopia, 14,32 and two in Malaysia; 16,33 and the remaining eight were performed in Qatar, 34 Egypt, 35 Algeria, 36 Saudi Arabia, 37 Nigeria, 38 Turkey, 39 Iran, 40 or Morocco. 41 All of the studies included both male and female patients, except the one performed by Farshori et al, which only included male patients 37 (Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%